PEMAKNAAN IKLAN DJARUM 76 VERSI TEMAN HIDUP (Analisis Semiotika Roland Barthes) - Kurniawan, Rudi; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Advertisement of tobacco products, including products that are limited in visualizing the advantages and beauty products, due to limited advertising rules and codes of conduct. In fact, the creators of advertising creates different ideas and more creative without any relevance between products with the idea of the ads displayed. Which attracted the attention of researchers is the Djarum 76 ad impressions to date, namely version Teman Hidup. A story about a woman who asked the genie figure to get a life partner, then granted his request was granted with a dog by the jinn. This research aims to determine the meaning Denotation, connotation, myth and also the messages contained in the ad impressions.This study used a qualitative descriptive approach. The method used in this research is the method of semiotic analysis, with the approach of semiotic analysis of Roland Barthes. The object of this research is Ad Djarum 76 version Teman Hidup. Which will be discussed in the form of units of analysis in the form of audio, visual and non-verbal expression in the ad impressions. So that would be obtained meaning denotation, connotation, and also myths and messages contained in the ad.This research obtains the result that the meaning of ad impressions Djarum 76 version Teman Hidup, the views of the meaning of denotation, connotation and also the myth of the ad shows the common occurrence in society. Jin character that is always displayed in the ad to grow reminding and brand awareness of the Djarum tobacco products 76. The results of the connotation meaning that male masculinity by not being obedient. As well as the myths in the community who still believe and rely ways to get instant desire, including business matchmaking through sacred objects, shamanism and allied with supernatural beings. Then the message to be conveyed in these ads is that the match can not be determined based on personal desires without any attempt to improve the quality of self and a mature attitude to accept the shortcomings, advantages and mutual understanding who we expect to be a life partner.Keywords: Advertising, Semiotics Analysis, Roland Barthes